"Zooming With": A Participatory Approach to the Use of Video Ethnography in Organizational Studies. (April 2018) - Jarrett, Michael; Liu, Feng
The desire to better understand the micro-behaviors of organizational actors has led to the increased use of video ethnography in management and qualitative research. Video captures detailed interactions and provides opportunities for researchers to link these to broader organizational processes. However, we argue there is a methodological gap. Studies that focus on the detail of the interactions "zoom in." Others that focus on the interactions in context "zoom out." But few go further and "zoom with"––that is, incorporate participants' interpretations of their video-recorded interactions. Our methodological contribution is that zooming with participants enhances research findings, helps to develop theory, and provides new insights for management practice. The article develops this idea by exploring and describing the method and applying it to top management teams, as well as showing how each focus provides different theoretical insights depending on which perspective or combination of perspectives is used. We conclude with the suggestion that a three-pronged approach to video ethnography be taken. The final section of the article discusses the implications for research and highlights the benefits of reflexivity in management practice.